2011
DOI: 10.1016/j.jacc.2011.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Renin-Angiotensin System Blockade Therapy on Outcome in Aortic Stenosis

Abstract: This large observational study suggests that ACEI/ARB therapy is associated with an improved survival and a lower risk of CV events in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(80 citation statements)
references
References 35 publications
1
75
1
3
Order By: Relevance
“…7,19 In a recent retrospective study, 25 patients with mild, moderate, and severe aortic stenosis who received angiotensin-converting enzyme inhibitors or angiotensin receptor blockers had lower all-cause mortality and cardiovascular event rates during a mean follow-up of 4.2 years than did patients who did not receive these medications. 25 β-Blockers are not routinely used in patients with aortic stenosis and have been considered unsafe because they depress myocardial function and can induce left ventricular failure. 1,7 However, a retrospective study 3 of the use of β-blockers in patients with asymptomatic severe aortic stenosis who were nonsurgically managed indicated that use of β-blockers was an independent predictor of improved survival.…”
Section: Medical Management Of Asymptomatic Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,19 In a recent retrospective study, 25 patients with mild, moderate, and severe aortic stenosis who received angiotensin-converting enzyme inhibitors or angiotensin receptor blockers had lower all-cause mortality and cardiovascular event rates during a mean follow-up of 4.2 years than did patients who did not receive these medications. 25 β-Blockers are not routinely used in patients with aortic stenosis and have been considered unsafe because they depress myocardial function and can induce left ventricular failure. 1,7 However, a retrospective study 3 of the use of β-blockers in patients with asymptomatic severe aortic stenosis who were nonsurgically managed indicated that use of β-blockers was an independent predictor of improved survival.…”
Section: Medical Management Of Asymptomatic Patientsmentioning
confidence: 99%
“…1 In patients without coronary artery disease, angina may be due to decreased subendocardial blood flow and/or increased myocardial oxygen demand associated with concentric hypertrophy. 2,25 Blood flow to the myocardium may be limited by insufficient capillary density into the hypertrophied left ventricular muscle and/or by endocardial compression due to increased filling pressures. 7,8 Syncope occurs because of decreased cerebral perfusion associated with decreased cardiac output or during exercise and times of decreased preload, such as after arising from a seated position; dehydration; and use of diuretics.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, a growing body of literature has reported that a high percentage of patients with significant AS do take antihypertensive and vasoactive medications without evident adverse effects. 5,10 Additionally, careful hemodynamic studies in patients with severe AS treated with single doses of vasodilating medications (captopril, nitroprusside, and sildenafil) have demonstrated the safety, tolerability, and, indeed, hemodynamic benefit of vasodilation in patients with severe symptomatic AS. [11][12][13] Those studies demonstrated that the particular vasodilating medications used result in a decrease in systemic vascular resistance and pulmonary capillary wedge pressure combined with an increase in stroke volume, but no change in heart rate.…”
Section: Article See P 1349mentioning
confidence: 99%
“…These observations suggest that ACE inhibitors may be used with caution in the treatment of hypertension in patients with AS. If they had been used before the diagnosis of AS with heart failure, hypertension or diabetic nephropathy and had been well tolerated by the patient, they should not be discontinued [21,[45][46][47][48]. Diuretic in AS should be used only in volume overload.…”
Section: Aortic Valve Replacement: When To Perform In Patients With Amentioning
confidence: 99%